Factors Influencing Right Hemisphere Engagement During Metaphor Comprehension - Diaz, Michele T.; Eppes, Anna (Frontiers in Psychology, 2018)
Although the left hemisphere is critical for language, clinical, behavioral, and neuroimaging research suggest that the right hemisphere also contributes to language comprehension. In particular, research has suggested that figurative language may be one type of language that preferentially engages right hemisphere regions. However, there is disagreement about whether these regions within the right hemisphere are sensitive to figurative language per se or to other factors that co-vary with figurativeness. In this article, we will review the neuroimaging literature on figurative language processing, focusing on metaphors, within the context of several theoretical perspectives that have been proposed about hemispheric function in language. Then we will examine three factors that may influence right hemisphere engagement: novelty, task difficulty, and context. We propose that factors that increase integration demands drive right hemisphere involvement in language processing, and that such recruitment is not limited to figurative language.